Experimental evidence for anisotropic response of a driven vortex lattice - Shalóm, D. E.; Pastoriza, H. (Elsevier, 2003)
Fil: Shalóm, D. E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina